Compatibilization of silicone/fluorosilicone blends by dynamic crosslinking and fumed silica addition. (4th July 2018) - Métivier, T.; Cassagnau, P.
Abstract: The aim of this work is to study the compatibility of silicone/fluorosilicone blends by exploring two compatibilization strategies. First, the crosslinking of the blend under shearing conditions leads to a reduction in the size of the fluorosilicone domain and hence to an effective stabilization of the morphology under shear and long time annealing. The refinement of the morphology in the dynamic crosslinking step is most likely due to a decrease in the viscosity ratio coming from preferential crosslinking of the fluorosilicone phase. However, the formation of a copolymer between silicone and fluorosilicone at the blend interface cannot be totally excluded. Secondly, the silicone/fluorosilicone blend was compatibilized by the addition of silica particles whose surface is hydrophilic or hydrophobic. Fumed hydrophilic silica allows to reduce the size of the fluorosilicone phase up to 500 nm while its hydrophobic counterpart is ineffective. This observation has been attributed to the specific hydrogen and dipolar interactions of the silicone and the CF3 group with the silanol present on the surface of the hydrophilic silica. The compatibilization mechanism is supposed to be due to a decrease in the interfacial tension and to a reduction of the coalescence phenomenon. Graphical abstract: Image 1 Highlights: The interfacial tension between Silicone and Fluorosilicone elastomers has been determined. The morphology size of silicone/fluorosilicone blends can be predicted from the Serpe's model. Silicone/fluorosilicone blends have been compatibilized by dynamic crosslinking. Silicone/fluorosilicone blends have been compatibilized by the addition of fumed hydrophilic silica.